2002
DOI: 10.1002/cne.10386
|View full text |Cite
|
Sign up to set email alerts
|

Granule neurons generated during development extend divergent axon collaterals to hippocampal area CA3

Abstract: Most excitatory intrahippocampal pathways are characterized by significant, highly ordered projections into the long, or septotemporal, hippocampal axis. However, the mossy fiber system, the excitatory projection by which the dentate gyrus projects to hippocampal area CA3, is considered an exception, being organized to innervate exclusively transversely oriented cortical layers of the hippocampus. In the present study, the anatomy of the rat mossy fiber system was investigated using axonal tracing techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…In contrast, the density of unlabeled pyknotic cells in the sgz, reflecting death of adult-born granule cells with a wide range of ages and maturity levels, was increased in all groups of rats that were removed from the housing facility the day before testing, while pyknotic cells in the outer gcl, where the oldest granule cells are located, were increased in all rats that were tested. Interestingly, the loss of these cells in the outer gcl, which are likely to have the largest axonal projections (Gaarskjaer, 1981;Hastings et al, 2002), is predicted by modeling to improve future learning by the network (Chambers et al, 2004).…”
Section: Cell Death and Cell Survivalmentioning
confidence: 99%
“…In contrast, the density of unlabeled pyknotic cells in the sgz, reflecting death of adult-born granule cells with a wide range of ages and maturity levels, was increased in all groups of rats that were removed from the housing facility the day before testing, while pyknotic cells in the outer gcl, where the oldest granule cells are located, were increased in all rats that were tested. Interestingly, the loss of these cells in the outer gcl, which are likely to have the largest axonal projections (Gaarskjaer, 1981;Hastings et al, 2002), is predicted by modeling to improve future learning by the network (Chambers et al, 2004).…”
Section: Cell Death and Cell Survivalmentioning
confidence: 99%
“…11,12,16 In the hippocampus, NSCs give rise to new granule cells that are functionally integrated in the existing neuronal network. [17][18][19][20][21] In addition to the main germinal zones of the CNS -the lateral subventricular zone and the hippocampus -small numbers of NSCs have also been identified in other brain regions, such as the subcortical white matter, 22 cerebral corte 23,24 and retina. 25 It has been suggested that different NSC populations exist in the CNS, and both cell intrinsic and local environmental signals contribute to the presence of regionally different NSC populations.…”
Section: Cells and Lineages Of The Cnsmentioning
confidence: 99%
“…The production of a substantial number of new granule cells has been demonstrated to continue into adulthood in rodents, nonhuman primates and humans (Cameron et al, 1993;Gould et al, 1997Gould et al, , 1999bEriksson et al, 1998;Kornack and Rakic, 1999;Roy et al, 2000;Seri et al, 2001). Newly formed granule cells migrate into the granular layer, send their axons (the mossy fibers) to CA3 field (Hastings and Gould, 1999;Markakis and Gage, 1999;Hastings et al, 2002), and mature into functional neurons that are incorporated into the major hippocampal circuit (granule cells-CA3-CA1 loop) (van Praag et al, 2002). These new neurons are thought to play a significant role in hippocampal synaptic plasticity (Snyder et al, 2001).…”
Section: Introductionmentioning
confidence: 98%